INTERNET JOURNALISM: BLOGS AND VLOGS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the evolution and impact of internet journalism, with a specific focus on blogs and vlogs. It analyzes how these formats have reshaped the landscape of modern media, allowing individuals to become content creators and journalists in their own right. The piece also considers the challenges and opportunities presented by this shift, particularly in terms of credibility, audience engagement, and the future of news reporting in a digital world.